Features of hydration of the composite system based on methyl silica AM-1 and dispersed Amanita muscaria mushrooms - T. V. Krupska; A. M. Datsiuk; M. I. Terebinska; S. O. Tellis; N. V. Vitiuk; I. V. Laguta; Qiliang Wei; Jinju Zheng; Weiyou Yang; V. V. Turov (Хімія, фізика та технологія поверхні)
Bioactive components of Amanita musсaria mushrooms are psilocybin, muscimol, muscarine and ibotenic acid, which have a long history of use in both traditional and non-traditional medicine. Natural psychoactive substances, depending on the dosage, can act as stimulants, hallucinogens or analgesics. Potentially promising products are composite systems created on the basis of highly dispersed silica and crushed natural mushroom Amanita musсaria. The aim of this work was to create a composite system in which for the hydrophobic composite AM-1/Amanita, on the one hand, a high affinity for water is preserved, and on the other hand, its clustering in the interparticle gaps of the composite and limited contact with the external environment are ensured.